2001
DOI: 10.1021/bi010232q
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of α-Helix to β-Sheet Transition in the Recombinant Prion Protein

Abstract: It is believed that the critical event in the pathogenesis of transmissible spongiform encephalopathies is the conversion of the prion protein from an alpha-helical form, PrP(C), to a beta-sheet-rich conformer, PrP(Sc). Recently, we have shown that incubation of the recombinant prion protein under mildly acidic conditions (pH 5 or below) in the presence of low concentrations of guanidine hydrochloride results in a transition to PrP(Sc)-like beta-sheet-rich oligomers that show fibrillar morphology and an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
138
2
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 41 publications
15
138
2
2
Order By: Relevance
“…In this regard, several groups have studied the conformational transition of different recombinant prion protein constructs into ␤-rich aggregates (40,(42)(43)(44)(45)(46)(47)(48). Some studies pointed to the formation of ␤-rich oligomers during the conformational transition of PrP (40,48).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several groups have studied the conformational transition of different recombinant prion protein constructs into ␤-rich aggregates (40,(42)(43)(44)(45)(46)(47)(48). Some studies pointed to the formation of ␤-rich oligomers during the conformational transition of PrP (40,48).…”
Section: Discussionmentioning
confidence: 99%
“…Such changes are readily studied using CD. For example, CD has been extensively used in the study of conformational transitions in peptides (see Figure 3) and in studies of the α-helix to β-sheet conversion in recombinant prion proteins induced by the addition of low concentrations of denaturants and/or salt at low pH (Morillas et al, 2001;Swietnicki et al, 2000).…”
Section: Solution Conditionsmentioning
confidence: 99%
“…23 The third well characterized form of PrP is a soluble oligomeric species favored at low pH ($4) under mild denaturing conditions with a high salt content. [24][25][26][27][28] CD indicates this low pH oligomer has a high b-sheet content, and solution NMR studies have shown that the N-terminal tail retains its mobility in this oligomeric form. 28 …”
Section: Introductionmentioning
confidence: 99%